2010
DOI: 10.1007/s10286-010-0106-2
|View full text |Cite
|
Sign up to set email alerts
|

Orthostatic heart rate responses after prolonged space flights

Abstract: Orthostatic tachycardia (POTS) can occur after space flights. We determined orthostatic heart rate responses in 18 cosmonauts before and 3-5 days after long-term space missions. Cosmonauts undergoing a cardiovascular training program in space experienced only moderate POTS after their return to earth. Cardiovascular countermeasures may have attenuated POTS. Another possible interpretation is that cardiovascular deconditioning is not sufficient to elicit full blown POTS in the absence of additional genetic or e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…In a recent study of 18 cosmonauts returning from long-duration flights, only three reported mild orthostatic symptoms during 10 minute standing (61). Neither orthostatic hypotension nor presyncope were observed in any subject.…”
Section: In-flight Countermeasuresmentioning
confidence: 99%
“…In a recent study of 18 cosmonauts returning from long-duration flights, only three reported mild orthostatic symptoms during 10 minute standing (61). Neither orthostatic hypotension nor presyncope were observed in any subject.…”
Section: In-flight Countermeasuresmentioning
confidence: 99%
“…When gravitational force is modified, as in the case of spaceflight, the physiology of human and animal body can experience various modifications altering the homeostasis balance (Cavolina et al ., ; Davis et al ., ; Zayzafoon et al ., ; Cancedda et al ., ; Tavella et al ., ). Bone disuse and bone loss effects can be considered some of the consequences related to spaceflight experience and they may represent an accelerated model of the osteoporosis disease in normal gravity conditions (Williams et al ., ; Vernikos and Schneider, ; Tavella et al ., ); moreover, space adaptation involves other complex changes in the organism physiology (Suganuma et al ., ; Iwamoto et al ., ; Gridley et al ., ; Tank et al ., ; Masini et al ., ; Rizzo et al ., ; Sandona et al ., ; Smith et al ., ).…”
Section: Introductionmentioning
confidence: 98%
“…4,11,12 Most patients are able to resume their normal daily activities, although recovery can be quite prolonged, and some patients with more severe symptoms can remain significantly symptomatic. 11 Recently, the role of deconditioning in perpetuating or even causing PoTS has been suggested, 13,14 and the beneficial effects of exercise training in ameliorating symptoms of orthostatic intolerance have been reported. 13,15 There are no other reported cases of PoTS responsive to immunoglobulin therapy nor it is suggested that immunoglobulin or corticosteroid therapy would be suitable for most patients with PoTS.…”
Section: Discussionmentioning
confidence: 99%